Motivasi Ibu-Ibu dalam Mengikuti Kegiatan Pengajian Majelis Taklim Desa Pasar Sipiongot Kecamatan Dolok Kabupaten Padang Lawas Utara - Hemmi Sari Harahap; Faisal Riza; Aulia Kamal (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
This articel discusses the motivation of mothers in participating in the activities of the Taklim Council in Sipiongot Village Dolok District, North Padang Lawas Regency. The method used in thus research is qualitative. The case studiens contained in this research produce descriptive data such a written words or questions and answers. Data collection is carried out using observation techniques, interview techniques and documentation techniques. The results of the research in this thesis are that the motivation of mothers in participating in the recitation activites of the Annur Taklim Council is very varied, some of them are because they want to increase their knowledge in the religious field, increase their insight, strengthen relationships between fellow congregation members, there are also provisions for the afterlife, because of something. Experienced after attenting the study. The factor is that mothers take part in the recitation of the Annur Taklim Assembly because of their own awareness and willingness, and also the distance between home and the palce of recitation is very clos, apart from that there are also those who are happy with the delivey given byy the uasdat because the material is prepared in detail, there is also encouragement from close friends, and the most infortant thing is to participate in the activities of the Annur Taklim Counsil solely hoping for the pleasure of Allah AWT.